Synthesis and Characterization of Nitrate-Based Fertilizers from Calcined Dolomite: Influence of Mass Loading and Stirring Time on Calcium and Magnesium Recovery. - Akhmad Maliki Brilliantino; Maria Florentina Estiningtyas; Sintha Soraya Santi; Erwan Adi Saputro (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This This study aims to synthesize calcium magnesium nitrate fertilizer (CaMg(NO?)?) from calcined dolomite and to evaluate the influence of dolomite mass and stirring time on the resulting calcium (Ca) and magnesium (Mg) content. Dolomite was selected as the primary raw material due to its wide availability in Indonesia and its naturally high Ca and Mg composition. The experimental procedure consisted of two main stages: thermal calcination of dolomite at 800°C for 4 hours, followed by a reaction with 100 mL of 68% nitric acid at 35°C under constant stirring at 300 rpm. The dolomite mass was varied between 5 and 25 g, while the stirring time ranged from 15 to 75 minutes. Product characterization was conducted using X-ray fluorescence (XRF) to quantify CaO and MgO contents. The results indicate that prolonged stirring enhances the dissolution of mineral components, leading to improved calcium recovery, although the effect of increasing dolomite mass does not exhibit a strictly proportional trend. The optimum condition was identified at 20 g of dolomite and 60 minutes of stirring, yielding 82.05% CaO and 0.88% MgO after normalization. The CaO content satisfies the minimum requirement specified in SNI 02-2806-1992 (?26%), whereas the MgO content remains below the threshold established by European Communities regulations (1994). Overall, the synthesized product is more appropriately categorized as a calcium-based fertilizer, given the predominance of calcium over magnesium in the final composition. These findings highlight the potential of calcined dolomite as a viable feedstock for nitrate-based fertilizer production, although further optimization is required to enhance magnesium incorporation.